Association between Family Structure, Parental Smoking, Friends Who Smoke, and Smoking Behavior in Adolescents with Asthma - Francisco Vázquez-Nava; José María Peinado-Herreros; Atenógenes H. Saldívar-Gonzalez; Ma Del Carmen Barrientos-Gómez; Francisco J. Beltrán-Guzmán; Jesus Perez-Martin; José A. Cordóva-Fernández; Carlos F. Vázquez-Rodríguez (The Scientific World Journal)
Recent investigations show that the smoking prevalence among asthmatic adolescents is higher than among healthy adolescents, and the causes that lead these asthmatic adolescents to smoke are unclear. We investigated the association between family structure, parental smoking, smoking friends, and smoking in asthmatic adolescents (n = 6,487). After adjusting for sex and age, logistic regression analyses showed that nonintact family structure, parental smoking, and smoking friends are associated with smoking in adolescents with and without asthma. Asthmatic adolescents who reside in the household of a nonintact family have a 1.90 times greater risk of smoking compared with those who live with both biological parents. It is important that parents who have children with asthma be made aware that the presence of smokers in the home and adolescent fraternization with smoking friends not only favor the worsening of asthma, but also induce the habit of smoking.